Static, Modal and Transient Analysis of Radial Arm using Ansys - Rahulji Dala, B. Gandhi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A computational capability is evolved for the gold standard design of radial drilling gadget shape to satisfy static stress and natural frequency necessities the use of finite element idealization. The radial drilling device structure is idealized with body elements and is analyzed by way of the usage of specific combos of move sectional shapes for the radial arm and the column. From the consequences acquired, the best mixture of cross sectional shapes is recommended for the structure. With this mixture of cross-sectional shapes, mathematical programming strategies are used to find the minimal weight design of the radial drilling device shape. A sensitivity analysis is carried out about the most excellent factor to locate the consequences of adjustments in layout variables on the structural weight and the reaction quantities.3D Modeling in CREO parametric software program and evaluation in ANSYS software.